Clinical and Functional Aspects and Improvement of Treatment of Year-Round Allergic Rhinitis in Children - Z., Narbayev; K., Narbayev (American Journal of Bioscience and Clinical Integrity, 2025)
Comorbid course of allergic rhinitis with bronchial asthma in the world in-depth study of the immunological aspects of pathogenesis and treatment a number of scientific studies aimed at improving the methods is being implemented. Bronchial allergic rhinitis in children Clinical and immunological features of a comorbid course with asthma studying the features of allergic rhinitis with bronchial asthma determination of levels and immunological research aimed at determining the interdependence of disorders The results have been published. Allergic rhinitis with bronchial methods of early diagnosis and treatment of the comorbid courseimprovement of the effectiveness of the differentiated treatment method assessment, allergen administered in children with these diseases Specific immunotherapy (SIT) is a pressing issue facing specialists in this field.